Celebrating Twenty Years of the Brazilian Symposium on Cardiovascular Physiology - Camille M. Balarini; Valdir A. Braga (Frontiers Media SA, 2017)
This e-book is dedicated to the celebration of 20 years of the Brazilian Symposium on Cardiovascular Physiology. In 1996 groups from the School of Medicine of Ribeirao Preto, University of Sao Paulo (FMRP-USP) and from the Federal University of Sao Paulo (UNIFESP) joined together to discuss cardiovascular physiology. In subsequent editions of the meeting, the participation of other groups from all over the country has grown and acquired the status of a national symposium. The participants now agree that the symposium should be itinerant and that the chair group is responsible for its organization. In 2016, we proudly reached the 20th edition of the Brazilian Symposium on Cardiovascular Physiology. It is certainly a memorable date and a great opportunity to share the accomplishments of Brazilian groups in the field of cardiovascular physiology.
English
Keywords: Cardiovascular Physiology; XX Brazilian Symposium on Cardiovascular Physiology; Renal function; Autonomic Nervous System; cardiac function; Vascular function